Mapping of Regional Strategic Issues in The Development Planning Documents (Case Study in Central Java) - Sofianto, Arif; Febrian, Lita; Ambarwati, Okki C; Risandewi, Tri (IOP conference series. Earth and environmental science, 2023)
In 2020, 21 regencies/cities (out of 35 regions) in Central Java will hold regional head elections. One of the consequences will be the preparation of the Regional Medium Term Development Plan (RPJMD) for the 2021-2026 period. The RPJMD was compiled during the Covid-19 pandemic, as well as the strengthening of other global issues such as the industrial revolution 4.0, society 5.0, advances in information technology, disruption and vulnerability to global economic crises, and food and energy issues. This research focuses on formulating strategic issues in the RPJMD document for the 21 regions to understand the framework, formulation process, and priority of strategic issues. This research is a descriptive study through a qualitative approach and is applied with practical purposes using desk study techniques. The research subjects were the RPJMD documents of 21 selected regencies/cities, especially in regional strategic issues. Data processing is done by classification technique, and data analysis is done by content analysis technique. The study results show that the strategic issues of concern are general, almost the same as the previous planning documents, such as bureaucratic reform, human resource capacity building, poverty (and unemployment), infrastructure, economic growth, and environmental natural resources. Some regions also place popular actual issues such as the Covd-19 pandemic and its recovery, the industrial revolution, smart cities, and SDGs, and only a small number of regions raise specific issues such as investment, village development, innovation, information technology, or sectoral issues such as agriculture, tourism, creative industries. This study concludes that the process of formulating strategic issues is still normative procedural, and general in nature, with a dominant technocratic approach, and needs to accommodate actual local issues and community discourse or aspirations. Formulating strategic issues also has no relation to regional development issues, more accommodating global, national issues and other planning documents without in-depth analysis.